2023
DOI: 10.26828/cannabis/2023/000171
|View full text |Cite
|
Sign up to set email alerts
|

Daily Relations Among Alcohol and Cannabis Co-Use, Simultaneous Use, and Negative Consequences: A Day-Level Latent Profile Analysis

Abstract: Objective: Concurrent and simultaneous cannabis and alcohol co-use confers risk for daily negative alcohol consequences. However, studies often treat co-use as a dichotomy, precluding examination of higher- and lower-risk co-use days. Additionally, little is known about specific alcohol consequences associated with daily co-use. Therefore, the current study 1) differentiated days based upon alcohol consumption, co-use, and simultaneous use, and 2) tested whether certain day-level use patterns conferred risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Although informative, this precludes examination of the impact that the quantities of alcohol and cannabis that are consumed have on the consequences associated with simultaneous use. Indeed, the few day-level studies that have distinguished among simultaneous use days that involve light versus heavy drinking have found that simultaneous use does not always confer greater risk for acute harms than alcohol use alone, as this may depend on the level of alcohol consumed (Boyle et al, 2023;Mallett et al, 2019;Waddell et al, 2023). For example, a recent daily diary study (Boyle et al, 2023) found that simultaneous use was only associated with elevated consequences when comparing light drinking simultaneous use days to light drinking alcohol-only days; on heavy drinking days, simultaneous use was not associated with greater consequences than alcohol-only use.…”
Section: Introductionmentioning
confidence: 99%
“…Although informative, this precludes examination of the impact that the quantities of alcohol and cannabis that are consumed have on the consequences associated with simultaneous use. Indeed, the few day-level studies that have distinguished among simultaneous use days that involve light versus heavy drinking have found that simultaneous use does not always confer greater risk for acute harms than alcohol use alone, as this may depend on the level of alcohol consumed (Boyle et al, 2023;Mallett et al, 2019;Waddell et al, 2023). For example, a recent daily diary study (Boyle et al, 2023) found that simultaneous use was only associated with elevated consequences when comparing light drinking simultaneous use days to light drinking alcohol-only days; on heavy drinking days, simultaneous use was not associated with greater consequences than alcohol-only use.…”
Section: Introductionmentioning
confidence: 99%